Reflecting on professional practice : capturing an industrial designer’s expertise to support the development of the sketching capabilities of novices - Storer, Ian (Design and Technology Education: An International Journal, 2008)
This paper reviews the importance of sketching to designers and clarifies the key techniques used at different stages of designing. The analysis of the author’s sketching expertise is described and a survey of undergraduate perceptions of sketching was carried out using the Nominal Group Technique (NGT) and a questionnaire. A revised strategy for the teaching and learning of sketching to first year industrial design and technology undergraduates is outlined and early observations of its implementation are reported.